Photocurable resin composition and molded articles containing the same, and electrical components

JP2026170631APending Publication Date: 2026-10-22ENPLAS CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025064284
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-04-09
Publication Date
2026-10-22

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、高い強度と、低い熱膨張率と、耐摩耗性と、を兼ね備える成形体や、これを得るための光硬化性樹脂組成物、および電気部品が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026170631000001
    Figure 2026170631000001
  • Figure 2026170631000002
    Figure 2026170631000002
  • Figure 2026170631000003
    Figure 2026170631000003
Patent Text Reader

Abstract

To provide a photocurable resin composition for obtaining a molded article that combines high strength, low thermal expansion coefficient, and wear resistance. [Solution] A photocurable resin composition that solves the above problem comprises (A) a polyfunctional acrylic resin containing (A1) a polycyclic aliphatic acrylic resin and (A2) an isocyanuric acid type acrylic resin, and (B) silica particles. In the photocurable resin composition, the amount of component (A1) relative to the total amount of component (A) is 20% by mass or more and 80% by mass or less, the amount of component (A2) relative to the total amount of component (A) is 20% by mass or more and 80% by mass or less, and the amount of silica particles (B) relative to the total amount of the photocurable resin composition is 20% by mass or more and 40% by mass or less. The average primary particle diameter of the silica particles (B) is 100 nm or less, and the aggregated particle diameter of the silica particles (B) measured by a specific method is 3 μm or more and 50 μm or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a photocurable resin composition, a molded article containing the same, and an electrical component. [Background technology]

[0002] In recent years, 3D printing has become known as a method for manufacturing parts and products of various shapes. Among the various printing methods, stereolithography using a photocurable resin composition containing a photocurable resin has the advantage of being able to quickly cure the resin into the desired shape. Various resins have been proposed as photocurable resins for use in stereolithography. For example, it has been proposed to use acrylates having an isocyanuric ring in stereolithography (for example, Patent Document 1).

[0003] However, resin molded articles obtained solely from photocurable resins often have insufficient mechanical strength, and improvements are needed. In response to this, it has been proposed to increase the mechanical strength of photopolymerizable resin compositions by adding fillers (for example, Patent Document 2). [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2022-70123 [Patent Document 2] Japanese Patent Publication No. 2023-140203 [Overview of the project] [Problems that the invention aims to solve]

[0005] However, in molded articles containing fillers, the mechanical strength may actually decrease or the wear resistance may be reduced depending on the particle size and aggregation state of the fillers. In addition, depending on the particle size of the fillers, the effect of reducing thermal expansion may not be sufficiently obtained.

[0006] The object of the present invention is to provide a molded article that combines high strength, a low coefficient of thermal expansion, and wear resistance, as well as a photocurable resin composition for obtaining the same, and an electrical component. [Means for solving the problem]

[0007] The present invention provides the following photocurable resin compositions. [1] A photocurable resin composition comprising (A) a polycyclic aliphatic acrylic resin and (A2) an isocyanuric acid type acrylic resin, (A) a polyfunctional acrylic resin, and (B) silica particles, wherein the amount of (A1) polycyclic aliphatic acrylic resin is 20% by mass or more and 80% by mass or less relative to the total amount of (A) polyfunctional acrylic resin, and the amount of (A2) isocyanuric acid type acrylic resin is 20% by mass or more and 80% by mass or less relative to the total amount of (A) polyfunctional acrylic resin, and the amount of (B) silica particles relative to the total amount of the photocurable resin composition A photocurable resin composition wherein the amount of silica particles is 20% by mass or more and 40% by mass or less, the average primary particle diameter of the (B) silica particles observed by a transmission electron microscope is 100 nm or less, and when the aggregated particles of the (B) silica particles are observed at two locations in the cross-section of the cured product of the photocurable resin composition at a magnification of 200x using an optical microscope, the diameters of the largest aggregated particle to the 10th largest aggregated particle present in each field of view are identified, and the average value of the diameters of a total of 20 aggregated particles is calculated, the average value is 3 μm or more and 50 μm or less. [2] The photocurable resin composition according to [1], wherein the (B) silica particles are surface-treated with a compound having a (meth)acryloyl group. [3] The photocurable resin composition according to [1] or [2], wherein the (A1) polycyclic aliphatic acrylic resin is tricyclodecanedimethanol diacrylate. [4] The photocurable resin composition according to any one of [1] to [3], wherein the (A2) isocyanuric acid type acrylic resin is a compound represented by the following general formula. [ka] (In the general formula, X 1 , X 2, and X 3 each independently represent a linking group having 1 to 20 carbon atoms which may contain oxygen, and R 1 and R 2 each independently represent a hydrogen atom or a methyl group, and Y represents a (meth)acryloyl group or a hydroxy group)

[0008] The present invention also provides the following molded article and electrical component. [5] A molded article comprising a cured product of the photocurable resin composition according to any one of the above [1] to [4]. [6] An electrical component comprising the molded article according to the above [5].

Effects of the Invention

[0009] According to the present invention, a molded article having high strength, a low coefficient of thermal expansion, and abrasion resistance, a photocurable resin composition for obtaining the same, and an electrical component are provided.

Modes for Carrying Out the Invention

[0010] The photocurable resin composition of the present invention is suitably used in a stereolithography method for producing a molded article by irradiating light. Hereinafter, the photocurable resin composition will be described by taking the case where the photocurable resin composition is used in a stereolithography method as an example. However, the use of the photocurable resin composition of the present invention is not limited thereto.

[0011] As described above, conventionally, addition of fillers to photocurable resin compositions has been studied, but it has been difficult to obtain a cured product that combines high strength, a low coefficient of thermal expansion, and abrasion resistance by simply adding a filler. The present inventors conducted intensive studies on this problem, and as a result, when general nanosilica having an average primary particle diameter of several nanometers to several hundreds of nanometers is added to a photocurable resin composition, although the abrasion resistance and strength of the cured product are improved, it is difficult to sufficiently obtain the effect of reducing the coefficient of thermal expansion. Furthermore, when a large amount of nanosilica is added, the photocurable resin composition tends to undergo thickening, which also causes the problem that a desired molded article is difficult to obtain. In addition, when microsilica having an average primary particle diameter of several microns to several hundreds of microns is added to a photocurable resin composition, although the coefficient of thermal expansion of the cured product is reduced, the abrasion resistance of the cured product tends to decrease. This is considered to be caused by the silica particles detaching or abrading the contacted member when in contact with another member.

[0012] In contrast, the photocurable resin composition of the present invention comprises (A) a polyfunctional acrylic resin and (B) silica particles, and satisfies the following five conditions (i) to (v). (i) The polyfunctional acrylic resin (A) contains 20% by mass or more and 80% by mass or less of the polycyclic aliphatic acrylic resin (A1). (ii) The polyfunctional acrylic resin (A) contains 20% by mass or more and 80% by mass or less of the isocyanuric acid type acrylic resin (A2). (iii) The amount of the silica particles (B) is 20% by mass or more and 40% by mass or less based on the total amount of the photocurable resin composition. (iv) The average primary particle diameter of the silica particles (B) observed with a transmission electron microscope is 100 nm or less. (v) With respect to two cross-sectional positions of a cured product of the photocurable resin composition, the aggregated particles of the silica particles (B) are observed with an optical microscope at a magnification of 200x, the diameters from the largest aggregated particle to the 10th largest aggregated particle present in each field of view are specified, and the average value of the diameters of a total of 20 aggregated particles is calculated, which is 3 μm or more and 50 μm or less.

[0013] In the photocurable resin composition of the present invention, as shown in condition (iii), a certain amount of (B) silica particles is included, and as shown in conditions (iv) and (v), the primary mean particle diameter of the (B) silica particles is 100 nm or less, and the average value of the diameter of the relatively large aggregated particles formed by the aggregation of the (B) silica particles falls within a predetermined range. In other words, the cured product of the photocurable resin composition of the present invention contains a predetermined amount of appropriately sized aggregated particles formed by the aggregation of sufficiently small (B) silica particles. Therefore, as shown in the examples described later, it is believed that the thermal expansion coefficient of the cured product will be lower, the strength will be higher, and the abrasion resistance will be better.

[0014] Furthermore, in the photocurable resin composition of the present invention, as shown in conditions (i) and (ii), the (A) polyfunctional acrylic resin contains predetermined amounts of (A1) polycyclic aliphatic acrylic resin and (A2) isocyanuric acid type acrylic resin. When (A1) polycyclic aliphatic acrylic resin and (A2) isocyanuric acid type acrylic resin are combined, they interact to form an acrylic network. Therefore, in the cured product of the photocurable resin composition of the present invention, this network enables even higher strength, lower thermal expansion coefficient, and higher abrasion resistance.

[0015] The photocurable resin composition of the present invention may contain (A) a polyfunctional acrylic resin and (B) silica particles, but usually also contains (C) a photopolymerization initiator. The components contained in the photocurable resin composition will be described in detail below.

[0016] (A) Polyfunctional acrylic resin In this specification, (A) polyfunctional acrylic resin means a resin having two or more (meth)acryloyl groups in one molecule. Also in this specification, (meth)acryloyl means methacryloyl, acryloyl, or both. The same applies to (meth)acrylate.

[0017] (A) The polyfunctional acrylic resin comprises at least (A1) a polycyclic aliphatic acrylic resin and (A2) an isocyanuric acid type acrylic resin, as described above. Within the limits that do not impair the objectives and effects of the present invention, (A) the polyfunctional acrylic resin may further contain known bifunctional or more functional acrylic resins other than (A1) a polycyclic aliphatic acrylic resin and (A2) an isocyanuric acid type acrylic resin (for example, pentaerythritol type acrylic resin, etc.). However, the total mass of (A1) a polycyclic aliphatic acrylic resin and (A2) an isocyanuric acid type acrylic resin relative to the total mass of (A) the polyfunctional acrylic resin is 40% by mass or more, preferably 80% by mass or more, and more preferably 90% by mass or more. When the total mass of (A1) a polycyclic aliphatic acrylic resin and (A2) an isocyanuric acid type acrylic resin is within this range, the amount of the network described above becomes sufficiently large, and the strength of the resulting molded article tends to increase further.

[0018] Furthermore, the total mass of (A) polyfunctional acrylic resin in the photocurable resin composition is preferably 60% by mass or more and 80% by mass or less, and more preferably 65% ​​by mass or more and 75% by mass or less. When the amount of (A) polyfunctional acrylic resin is 60% by mass or more, (B) silica particles are more easily bound, and the strength of the photocurable resin composition tends to increase further. On the other hand, when the amount of (A) polyfunctional acrylic resin is 80% by mass or less, the amount of (B) silica particles and the (C) photopolymerization initiator described later becomes relatively larger. As a result, the thermal expansion coefficient of the cured product becomes even lower, and the photocurability of the photocurable resin improves.

[0019] (A1) Polycyclic aliphatic acrylic resin In this specification, "polycyclic aliphatic acrylic resin" means a resin having a polycyclic aliphatic structure and two or more (meth)acryloyl groups. The (A1) polycyclic aliphatic acrylic resin may be a monomer, an oligomer, or a polymer, but considering the viscosity of the photocurable resin composition and its interaction with the (A2) isocyanuric acid type acrylic resin described later, it is preferable that it be a monomer. The (A) polyfunctional acrylic resin may contain only one type of (A1) polycyclic aliphatic acrylic resin, or it may contain two or more types.

[0020] Here, the number of rings in the polycyclic aliphatic structure should be two or more, but 2 to 5 is preferred, 2 to 4 is more preferred, and 2 or 3 is even more preferred. Examples of polycyclic aliphatic structures include condensed polycyclic cycloalkane structures such as bicycloundecane, tricyclodecane, norbornane, adamantane, and decahydronaphthalene; and spirocyclic cycloalkane structures such as spiro[3,4]octane, spiro[4,4]nonane, and spiro[4,5]decane. Among these, condensed polycyclic cycloalkane structures are preferred, and tricyclodecane structures are more preferred.

[0021] On the other hand, the number of (meth)acryloyl groups may be two or more, but 2 to 6 is preferred, 2 to 4 is more preferred, and 2 or 3 is even more preferred. The (meth)acryloyl groups may be directly bonded to the above polycyclic aliphatic structure, or they may be bonded via linking groups such as alkylene groups or alkylene oxy groups.

[0022] (A1)Specific examples of polycyclic aliphatic acrylic resins include tricyclodecanediethanol di(meth)acrylate, adamantanediol di(meth)acrylate, and adamantanetriol di(meth)acrylate. Among these, tricyclodecanediethanol di(meth)acrylate is particularly preferred in that it readily interacts with the isocyanuric acid type acrylic resin described later (A2) to form the aforementioned network.

[0023] The amount of (A1) polycyclic aliphatic acrylic resin may be 20% by mass or more and 80% by mass or less relative to the total mass of the (A) polyfunctional acrylic resin, and is more preferably 30% by mass or more and 70% by mass or less. As described above, when the amount of the (A1) polycyclic aliphatic acrylic resin is within the above range, the strength of the cured product obtained from the photocurable resin composition is sufficiently enhanced.

[0024] ·(A2) Isocyanuric acid type acrylic resin The (A2) isocyanuric acid type acrylic resin is a resin having an isocyanuric ring and two or more (meth)acryloyl groups. The (A2) isocyanuric acid type acrylic resin may be a monomer, an oligomer, or a polymer, but from the viewpoints of the viscosity of the photocurable resin composition and the interaction with the (A1) polycyclic aliphatic acrylic resin, it is preferably a monomer. The (A) polyfunctional acrylic resin may contain only one type of the (A2) isocyanuric acid type acrylic resin, or may contain two or more types thereof.

[0025] Here, the number of isocyanuric rings contained in the (A2) isocyanuric acid type acrylic resin may be 1 or more, and may be 2 or more, but is usually 1. In addition, the number of (meth)acryloyl groups contained in the (A2) isocyanuric acid type acrylic resin may be 2 or more, usually 2 or 3, and preferably 3. When the (A2) isocyanuric acid type acrylic resin has three (meth)acryloyl groups, the isocyanuric acid type acrylic resin easily forms the above-mentioned network in the cured product, and the strength of the cured product (molded body) is further likely to be enhanced.

[0026] Examples of the (A2) isocyanuric acid type acrylic resin include compounds represented by the following general formula.

Formula

[0027] In the above general formula, R 1 and R 2 Each of these independently represents either a hydrogen atom or a methyl group. 1 and R 2 These may be the same or different. Furthermore, in the above general formula, Y represents a (meth)acryloyl group or a hydroxyl group.

[0028] (A2) The isocyanuric acid type acrylic resin may be a synthetic product or a commercially available product. Examples of commercially available (A2) isocyanuric acid type acrylic resins having three (meth)acryloyl groups include NK ester A-9300S and NK ester A-9300-1CL (both manufactured by Shin Nakamura Chemical Industry Co., Ltd.), and Aronics M-327 (manufactured by Toagosei Co., Ltd.). Examples of commercially available (A2) isocyanuric acid type acrylic resins having two (meth)acryloyl groups include Aronics M-215 (manufactured by Toagosei Co., Ltd.). Furthermore, examples of commercially available mixtures of (A2) isocyanuric acid type acrylic resin having three (meth)acryloyl groups and (A2) isocyanuric acid type acrylic resin having two (meth)acryloyl groups include Arronix M-313 and Arronix M-315 (both manufactured by Toagosei Co., Ltd.).

[0029] (A2) Among the isocyanuric acid type acrylic resins, the compound represented by the following formula is particularly preferred in that it readily interacts with the (A1) polycyclic aliphatic type acrylic resin to form a desired network. [ka]

[0030] (A2) The amount of isocyanuric acid type acrylic resin may be 20% to 80% by mass relative to the total mass of (A) polyfunctional acrylic resin, and more preferably 30% to 70% by mass. As described above, when the amount of (A2) isocyanuric acid type acrylic resin is within this range, the strength of the cured product (molded article) obtained from the photocurable resin composition tends to increase further.

[0031] (B) Silica particles (B) Silica particles are silica-containing particles whose average primary particle diameter observed by a transmission electron microscope is 100 nm or less, as described above. In this specification, the average primary particle diameter of (B) silica particles refers to the average primary particle diameter of (B) silica particles in powder form before mixing with the (A) polyfunctional acrylic resin, etc., as described above. Specifically, the average primary particle diameter is measured by the following method: Multiple silica particles in a dry state are imaged using a transmission electron microscope. Twenty silica particles are randomly selected from the obtained images, and the particle diameter of each is determined. If the shape of each silica particle in the captured image is not perfectly circular, the maximum diameter of each particle is measured as the major axis, and the diameter perpendicular to it is measured as the minor axis. Then, (major axis + minor axis) / 2 is adopted as the particle diameter of the particle. The average value of the particle diameters of the 20 silica particles is then taken as the average primary particle diameter of the (B) silica particles.

[0032] (B) The average primary particle diameter of the silica particles is 100 nm or less. As mentioned above, when the average primary particle diameter of the silica particles is 100 nm or less, when the cured product of the photocurable resin composition rubs against other components, the other components are less likely to be abraded, resulting in good abrasion resistance. Furthermore, even if the silica particles fall off due to rubbing against other components, the amount of the detached portion is small, so it does not significantly affect the strength of the cured product. The average primary particle diameter of the silica particles is preferably 1 nm or more and 100 nm or less, more preferably 3 nm or more and 50 nm or less, and even more preferably 5 nm or more and 20 nm or less. The shape of the primary particles of the silica is not particularly limited, but it is preferably spherical.

[0033] Furthermore, the average diameter of the aggregated particles of (B) silica particles is between 3 μm and 50 μm. The average diameter of the aggregated particles of (B) silica particles can be measured by the following method: Observe the aggregated particles of (B) silica particles at two locations on the cross-section of the cured product obtained from the photocurable resin composition using an optical microscope at a magnification of 200x. Identify the diameters of the largest aggregated particle and the tenth largest aggregated particle present in each field of view, and calculate the average value of the diameters of these 20 aggregated particles. This average value (hereinafter, this average value will also be referred to as the "aggregated particle diameter") is then used.

[0034] The detailed measurement method for the aggregated particle diameter is as follows: First, a photocurable resin composition is cured by irradiating it with light of a wavelength of 365 nm for 5 seconds to prepare a plate-shaped sample with a thickness of 1 mm. The obtained plate-shaped sample (cured material) is embedded in resin, and then the embedded material is polished so that the cross-section of the cured material is exposed. Two locations on the exposed cured material are imaged at a magnification of 200x using an optical microscope. The aggregated particles of (B) silica particles present in each field of view of the two obtained images are observed, and the diameters of the largest aggregated particle to the 10th largest aggregated particle are determined. If the aggregated particles in the obtained images are not perfectly circular, the largest diameter of the aggregated particle is taken as the major axis, and the diameter perpendicular to it is taken as the minor axis. Then, (major axis + minor axis) / 2 is taken as the diameter of the aggregated particle. The average value of the diameters of these 20 aggregated particles is then calculated and taken as the aggregated particle diameter.

[0035] When the aggregated particle size obtained by the above method is 3 μm or more and 50 μm or less, the resulting cured product exhibits good bending strength and wear resistance, as well as a low coefficient of thermal expansion. Preferably, the aggregated particle size is 4 μm or more and 40 μm or less, and more preferably 5 μm or more and 35 μm or less.

[0036] The cohesiveness of (B) silica particles can be adjusted by surface treatment of the (B) silica particles. Examples of (B) silica particles with such cohesiveness include fumed silica whose surface has been modified with a silane coupling agent.

[0037] The type of silane coupling agent is not particularly limited, as long as it has affinity for (A) polyfunctional acrylic resin and (B) silica particles and is capable of moderately agglomerating (B) silica particles. Examples of silane coupling agents include amino group-containing silane coupling agents such as N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and 3-aminopropyltriethoxysilane; vinyl group-containing silane coupling agents such as vinyltrimethoxysilane, vinyltriethoxysilane, and diethoxymethylvinylsilane; and 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane. These include (meth)acryloyl group-containing silane coupling agents such as 3-acryloxypropyltrimethoxysilane; isocyanate group-containing silane coupling agents such as 3-isocyanatetopropyltriethoxysilane; epoxy group-containing silane coupling agents such as 3-glycidoxypropyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane; ureido group-containing silane coupling agents such as 3-ureidopropyltriethoxysilane; and mercapto group-containing silane coupling agents such as 3-mercaptopropyltrimethoxysilane. These can be used individually or in combination of two or more.

[0038] Among the silane coupling agents mentioned above, compounds having a (meth)acryloyl group, i.e., (meth)acryloyl group-containing silane coupling agents, are preferred because they have good affinity with (A) polyfunctional acrylic resin and are more likely to achieve the above-mentioned aggregated particle size. Furthermore, when the silane coupling agent has a (meth)acryloyl group, the silane coupling agent polymerizes with the above-mentioned (A) polyfunctional acrylic resin. This makes it easier for the aggregated particles of (B) silica particles to be dispersed more uniformly within the (A) polyfunctional acrylic resin. An example of (B) silica particles that are more likely to achieve the above-mentioned aggregated particle size is AEROSIL R7200, manufactured by Nippon Aerosil Co., Ltd.

[0039] (B) The amount of silica particles may be 10% by mass or more and 40% by mass or less relative to the total mass of the photocurable resin composition, and preferably 20% by mass or more and 38% by mass or less. As described above, when the amount of silica particles (B) is within this range, the thermal expansion of the resulting molded article becomes sufficiently low, and furthermore, the strength of the resulting molded article is increased and the abrasion resistance is improved.

[0040] (C) Photopolymerization initiator (C) The photopolymerization initiator is any compound that can absorb light (e.g., ultraviolet light or visible light, etc.) irradiated when curing the photocurable resin composition to generate active species and initiate polymerization of the above-mentioned (A) polyfunctional acrylic resin, etc. The photocurable resin composition may contain only one type of (C) photopolymerization initiator, or it may contain two or more types.

[0041] (C) Examples of photopolymerization initiators include alkylphenone-based radical polymerization initiators, acylphosphine oxide-based radical polymerization initiators, and oxime ester-based radical polymerization initiators. Examples of alkylphenone-based photopolymerization initiators include 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxycyclohexylphenyl ketone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)-benzyl]phenyl}-2-methylpropane-1-one, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, and 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone. On the other hand, examples of acylphosphine oxide-based photopolymerization initiators include bisphenyl(2,4,6-trimethylbenzoyl)phosphine oxide and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide. Examples of oxime ester-based radical polymerization initiators include 2-benzoyloxyimino-4'-(phenylthio)octanophenone and 6-[1-(acetyloxyimino)ethyl]-9-ethyl-9H-carbazole-3-yl-2-methylphenyl ketone.

[0042] The amount of (C) photopolymerization initiator in the photocurable resin composition is preferably 0.5 parts by mass or more and 3.0 parts by mass or less, and more preferably 0.7 parts by mass or more and 2.0 parts by mass or less, per 100 parts by mass of the total mass of the photocurable resin (the above-mentioned (A) polyfunctional acrylic resin, etc.). When the amount of (C) photopolymerization initiator is within this range, it is possible to efficiently cure the photocurable resin composition.

[0043] (D) Other ingredients The photocurable resin composition may further contain components other than (A) polyfunctional acrylic resin, (B) silica particles, and (C) photopolymerization initiator, to the extent that it does not impair the objectives and effects of the present invention. Examples of other components include other photocurable resins (e.g., monofunctional acrylic resins) other than (A) polyfunctional acrylic resin, other curable resins such as epoxy resins, and various additives. Examples of additives include dispersion stabilizers, colorants, UV absorbers, antioxidants, polymerization inhibitors, defoamers, fillers, photosensitizers, toughening agents, etc.

[0044] (Viscosity of photocurable resin composition) The viscosity of the photocurable resin composition is appropriately selected depending on the type of stereolithography method. For example, in the additive manufacturing method described later, the viscosity of the photocurable resin composition at 25°C is usually preferably between 1 Pa·s and 1000 Pa·s, and more preferably between 10 Pa·s and 800 Pa·s. The above viscosity is measured using a rheometer (e.g., Discovery HR-2 from TA Instruments) at a shear rate of 1 (1 / s), and read after the rotation has stabilized (e.g., after 90 seconds). When the viscosity of the photocurable resin composition is within this range, the fluidity of the photocurable resin composition during stereolithography tends to be appropriate.

[0045] (Method for preparing a photocurable resin composition) The method of preparing the above-mentioned photocurable resin composition is not particularly limited, as long as it is possible to uniformly mix (A) a polyfunctional acrylic resin, (B) silica particles, and (C) a photopolymerization initiator, and other components as needed. For example, all components may be mixed at once. Alternatively, (A) the polyfunctional acrylic resin and (C) the photopolymerization initiator may be mixed first, and then (B) the silica particles and other components may be mixed. The mixing method can be the same as known stirring or kneading methods.

[0046] (Stereolithography method using photocurable resin composition) The above-mentioned photocurable resin composition can be used in various stereolithography methods, but one example is the following additive manufacturing method.

[0047] In this method, a photocurable resin composition is supplied onto a stage to form a layer (first layer) of a desired thickness made of the photocurable resin composition. At this time, the method of supplying the photocurable resin composition is not particularly limited, and for example, a method using a T-die can be used. The surface of the photocurable resin composition supplied from the T-die may be smoothed with a squeegee or doctor knife as needed. Then, a predetermined area of ​​the first layer made of the photocurable resin composition is irradiated with light to cure the photocurable resin composition in the irradiated area. The method of light irradiation is not particularly limited, and for example, laser light may be scanned, or the area may be exposed all at once via a mask or the like. At this time, the wavelength of the light to be irradiated is not particularly limited and is appropriately selected according to the type of photopolymerization initiator described above, but for example, light with a wavelength of 100 nm to 405 nm is preferred.

[0048] Further, a photocurable resin composition is supplied onto the first layer of cured material to form a layer of a desired thickness (second layer). Then, light is irradiated onto a desired area of ​​the second layer in the same manner as above to cure the photocurable resin composition. By repeating these steps, a molded article containing the cured product of the photocurable resin composition is obtained.

[0049] Furthermore, after or during the production of the molded body, heat treatment may be performed as needed to accelerate the curing of the photocurable resin composition.

[0050] (Uses of molded products) Molded articles containing the cured product of the above-mentioned photocurable resin composition have high mechanical strength, good wear resistance, and a low coefficient of thermal expansion, as described above. Therefore, they can be used in a variety of applications, including electrical components, electronic equipment, medical equipment, electrical appliances, robot-related products, and vehicle-related products. Among these, they are particularly useful in the manufacture of electrical components, where composite parts are often produced by combining molded articles with metals. [Examples]

[0051] The present invention will be described below using examples and comparative examples, but the present invention is not limited in any way to the following examples.

[0052] 1. Preparation of materials The following materials were used in the examples and comparative examples.

[0053] (A) Polyfunctional acrylic resin (A1) Polycyclic aliphatic acrylic resin • IRR-214K (Tricyclodecanedimethanol diacrylate, manufactured by Daicel Ornex) (A2) Isocyanuric acid type acrylic resin ·A-9300S (manufactured by Shin-Nakamura Chemical Co., Ltd.)

[0054] (B) Silica particles • R7200 (methacrylate silane surface treatment, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL R7200) • R711 (methacrylate silane surface treatment, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL R711) • AdmaFine SC2500-SMJ (manufactured by Admatex Co., Ltd.)

[0055] (C) Photopolymerization initiator • Omnirad819 (manufactured by IGM Resins)

[0056] 2. Preparation of photocurable resin composition and production of cured product (Example 1) <Preparation of photocurable resin composition> The types of (A) polyfunctional acrylic resins and (C) photopolymerization initiators shown in Table 1 were separated into beakers in the mass ratios shown in Table 1. Specifically, 70 parts by mass of (A1) polycyclic aliphatic acrylic resin (tricyclodecanedimethanol diacrylate), 30 parts by mass of (A2) isocyanuric acid type acrylic resin (tris[2-(acryloyloxy)ethyl]isocyanurate), and 0.7 parts by mass of (C) photopolymerization initiator (phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide) were separated into beakers. These were heated at 70°C for 30 minutes while stirring, and it was confirmed that a homogeneous solution was obtained. Then, 43 parts by mass of (B) silica particles (R7200) were added, and the mixture was kneaded and degassed using a planetary mixer SK-300TVS (manufactured by Shashin Kagaku Co., Ltd.). This prepared a photocurable resin composition.

[0057] <Preparation of molded products (cured products)> A 1mm thick donut-shaped spacer (a φ80mm circular spacer with a φ50mm hole in the center) was placed on a mold-release-treated plate-shaped substrate, and the resin composition was poured into the hole in the spacer. Then, the inner half was masked with black tape and sandwiched between mold-release-treated glass plates. Then, from one side of the glass plate, light with a wavelength of 365nm was irradiated with a UV lamp for 5 seconds. The uncured portion was wiped off with Technowipe, the uncured material was removed with an air blower, and then the edges were wiped with ethanol to obtain a molded body (cured product).

[0058] (Examples 2-4, Comparative Examples 1-6) A photocurable resin composition was prepared in the same manner as in Example 1, except that (A) the amount of polyfunctional acrylic resin, (B) the type, aggregate particle size, and amount of silica particles, and (C) the amount of photopolymerization initiator were as shown in Table 1 below. A molded article (cured product) was then produced.

[0059] 3. Evaluation The primary particle size and aggregated particle size of each (B) silica particle were evaluated by the following method. Furthermore, the thermal expansion coefficient, flexural strength, and abrasion resistance of the cured product were evaluated by the following method.

[0060] <(B) Measurement of the average primary particle size of silica particles> Silica particles were photographed using a transmission electron microscope before being mixed with a photocurable resin or the like. From the obtained images, 20 particles were randomly selected and their particle diameters were measured. In cases where the silica particles were not perfectly round in the images, the largest diameter of each particle was defined as the major axis, and the diameter perpendicular to it was defined as the minor axis. Then, (major axis + minor axis) / 2 was adopted as the particle diameter of that particle. The average value of the particle diameters of the 20 silica particles was then defined as the average primary particle diameter.

[0061] <Measurement of aggregated silica particle size> After embedding the aforementioned molded body in resin, the embedding was polished to form a smooth surface exposing the molded body. Two locations on this surface where large particles were unevenly distributed were observed and photographed using an optical microscope at 200x magnification. Aggregated silica particles were observed in the two images taken, and the particle sizes from the largest to the tenth largest were identified. If the photographed aggregated particles were not perfectly circular, the largest diameter of the aggregated particle was defined as the major axis, and the length perpendicular to it was defined as the minor axis. The diameter of the aggregated particle was then calculated as (major axis + minor axis) / 2. The average of the diameters of 20 aggregated particles was then defined as the average particle size of the aggregated particles. If aggregated particles could not be observed with an optical microscope at 200x magnification, the magnification was increased to 1000x. If aggregated particles still could not be observed, the aggregated particle size was considered to be less than 3 μm.

[0062] <Measurement of thermal expansion coefficient> The thermal expansion coefficient was evaluated using a ThermoplusEV02 TMA8311 / LN2 thermal analyzer (Rigaku Corporation) with a test piece cut from the aforementioned molded body to a size of 2.8 mm × 15.0 mm using a small CO2 laser processing machine HAJIME CL1 (O-Laser Co., Ltd.), in accordance with JIS K-7197. Specifically, thermal analysis was performed under a nitrogen atmosphere with a load of -49.0 mM and a heating rate of 5°C / min to determine the thermal expansion coefficient in the range of -40°C to 150°C.

[0063] <Bending strength measurement> The bending strength was measured using a universal testing machine (manufactured by Shimadzu Corporation). Specifically, a three-point bending test was performed using a jig with a span of 10 mm and upper and lower indenter diameters of 0.1 mm, at a crosshead speed of 10 mm / min, to measure the bending strength of the molded body described above. The sample size N=5 was used, and the average of the maximum stresses in the tests was taken as the bending strength value.

[0064] <Abrasion Test> Abrasion resistance was tested by rubbing the end face of the fabricated molded body perpendicularly against a 0.5 mm thick anodized aluminum plate. A circle (○) indicated no dust was produced from the hardened material, a small amount of dust was produced (△), and a large amount of dust was produced (×). △ and ○ represent good results.

[0065] 4.Results [Table 1]

[0066] As shown in Table 1 above, aggregated silica particles could not be observed in Comparative Example 1 and Comparative Example 2. In Comparative Example 1, the thickening of the resin composition prevented the production of a molded article. On the other hand, in Comparative Example 2, the thickening of the resin composition generated a large number of voids, which is thought to have reduced the bending strength. Furthermore, the wear resistance could not be evaluated due to the voids.

[0067] In Comparative Example 3, the aggregated particle diameter of the silica particles was excessively large, exceeding 50 μm. Therefore, the portion containing the aggregated particles was brittle, resulting in low flexural strength. Furthermore, for similar reasons, the wear resistance was likely low. In Comparative Example 4, the average primary particle diameter of the silica particles was large, while the aggregated particle diameter was small. Silica particles with a large average primary particle diameter are prone to wear, resulting in low wear resistance.

[0068] In Comparative Examples 5 and 6, the acrylic resin had difficulty forming a suitable network structure, resulting in low flexural strength in both cases, and in Comparative Example 6, the abrasion resistance was also reduced.

[0069] In contrast, Examples 1 to 4, which contained cyclic aliphatic acrylic resin and isocyanuric acid acrylic resin in appropriate proportions, and in which the primary particle size and aggregated particle size of silica particles fell within the desired range, showed excellent performance in terms of thermal expansion coefficient, flexural strength, and abrasion resistance. [Industrial applicability]

[0070] The photocurable resin composition of the present invention provides a molded article that combines high strength, low thermal expansion coefficient, and wear resistance. This molded article can be used in a variety of applications, such as electrical components.

Claims

1. (A) A polyfunctional acrylic resin comprising (A1) a polycyclic aliphatic acrylic resin and (A2) an isocyanuric acid type acrylic resin, (B) Silica particles and A photocurable resin composition containing, The amount of (A1) polycyclic aliphatic acrylic resin relative to the total amount of (A) polyfunctional acrylic resin is 20% by mass or more and 80% by mass or less. The amount of (A2) isocyanuric acid type acrylic resin relative to the total amount of (A) polyfunctional acrylic resin is 20% by mass or more and 80% by mass or less. The amount of (B) silica particles relative to the total amount of the photocurable resin composition is 20% by mass or more and 40% by mass or less. The average primary particle diameter of the silica particles (B) observed by a transmission electron microscope is 100 nm or less. When the aggregated silica particles (B) were observed at two cross-sections of the cured product of the photocurable resin composition using an optical microscope at a magnification of 200x, and the diameters of the largest aggregated particle to the tenth largest aggregated particle within each field of view were identified, the average value of the diameters of the 20 aggregated particles was calculated, and the average value was found to be between 3 μm and 50 μm. Photocurable resin composition.

2. The (B) silica particles are surface-treated with a compound having a (meth)acryloyl group. The photocurable resin composition according to claim 1.

3. The (A1) polycyclic aliphatic acrylic resin is tricyclodecanedimethanol diacrylate. The photocurable resin composition according to claim 1.

4. The (A2) isocyanuric acid type acrylic resin is a compound represented by the following general formula: The photocurable resin composition according to claim 1. 【Chemistry 1】 (In the general formula, X 1 , X 2 , and X 3 Each of these independently represents a linking group having 1 to 20 carbon atoms and which may contain oxygen. R 1 and R 2 Each of these independently represents either a hydrogen atom or a methyl group. (Y represents a (meth)acryloyl group or a hydroxyl group.)

5. A cured product of a photocurable resin composition according to any one of claims 1 to 4, Molded body.

6. A molded article comprising the one described in claim 5, Electrical components.

Citation Information

Patent Citations

  • Photocurable resin composition and method for producing optically shaped article using the same

    JP2022070123A

  • Curable composition, three-dimensional object producing method, three-dimensional object producing apparatus, and artificial tooth object

    JP2023140203A